The Influence of Product Quality and Promotion on Consumer Satisfaction on Longo Products - Chelsi Goris Manek; Christina Yanita Setyawati (Universitas Ciputra Surabaya, 2022)
The fashion industry in Indonesia especially clothing gets the highest growth among other industrial sectors. That thing of course makes entrepreneur are required to be able to maintain customer satisfaction in order to survive in the midst of many business competitors in similar field.. Longo is a business that runs in fashion especially t-shirts. The purpose of this research is to find out the influence of product quality and promotion on consumer satisfaction. This research is quantitative with linear regression analysis method. The population of this research is Longo consumers. This research uses purposive sampling technique by taking the sample of 82 people. Data collection is done by using questionnaires which are measured using Likert scale. The result of the research shows that product quality influences positive and significant on consumer satisfaction, and promotion influences positive and significant on consumer satisfaction.